A participação de aluno adulto maduro em cursos técnicos subsequentes do Colégio Técnico Industrial de Santa Maria - Peixoto, Nirvan Hofstadler (2021)
This study was developed together with the Graduate Program in Professional and Technological Education of the Santa Maria Industrial Technical College of the Federal University of Santa Maria, Academic Master's, research line in Innovation for Professional and Technological Education (EPT). The general objective of this work was to verify the participation of mature adults in subsequent courses in electrotechnics, electromechanics and mechanics at CTISM and how their participation impacts the teaching of subsequent courses. The present study is justified for contributing to the school in the identification of the age group of the public that seeks EPT, as its participation changes the forms of teaching and proposes alternatives to work with generational diversity. Mature adults were considered to be those aged 35 or over, which is based on the psychosocial stages of human development proposed by Erikson (1972). The research was carried out through information collected at the CTISM School Records Secretariat, from 2011 to 2019 and through electronic research conducted with teachers and students of the referred courses. The results pointed to the need for a closer look at mature students, in view of their growing demand for technical courses, the different experiences and expectations of mature students compared to young students. And we conclude the number of mature students has a tendency to increase over the years and who seek EPT for their personal fulfillment and insertion in the job market.